Go Green program as an effort to enhance UI civitas awareness towards sustainable campus. Issue 5 (March 2021) - Bowolaksono, A; Kholis, N; Wardani, W K; Pradipta, E; Lestari, F; Patria, M P; Priambodo, R
Abstract: Civitas activities in the campus environment both from lectures and other supporting activities can produce waste. The civitas lifestyle often influences the amount of waste produced, such as inefficient use of paper and disposable packaging. Civitas awareness related to the impact of the lifestyle on the waste generated needs to be increased to support a sustainable campus. Some ways that can be done are by conducting socialization, implementing regulations, and conducting waste sorting programs. Based on the efforts that have been made, the amount of waste generated in 2019 has decreased compared to 2018. This is influenced by the sustainable campus policies implemented at Universitas Indonesia which began to be applied at the end of 2018.